PENGGUNAAN MEDIA POSTER DALAM PEMBELAJARAN FISIKA UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS VIII SMP NEGERI 2 KUANTAN HILIR SEBERANG - Dodi Sutrisno Sutrisno; Zuhdi Ma’aruf Ma’aruf; Yennita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Indonesian education system generally still less to provide opportunities for the development of student creativity, so the percentage of successful student learning outcomes through the sense of sight is a condition of early elections poster in teaching physics to improve students creativity. This research aims to describe the increase in ability to think creatively and student creativity of class VIII SMPN 2 Kuantan Hilir Seberang of physics by using media poster. This research was conducted in SMPN 2 Kuantan Hilir Seberang precisely in maret to June 2015. The subjects were students and VIIIC VIIIA class of 60 students composed of two classes that have been in the homogeneity test. Form the research is pre-experimental with design intact-group comparison. The instrument of data collection in this research is a test the ability of creative thinking and creativity questionnaire. Analysis of the data in this research is a descriptive analysis. The results were obtained using the student ability to think creatively poster media has increased and creativity of the students use the poster media also increased. It can be concluded the use of posters can enhance the creativity student class VIII SMPN 2 Kuantan Hilir Seberang in the subject matter vibrations and waves. Key Words: Creativity, Media Posters, vibration and wave